The Effectiveness of Mobile Device-Based Digital Interventions on the Risk Factors of Diabetes Mellitus Control in the Industrial Revolution 4.0 - Ratna Kuatiningsari; Fatqiatul Wulandari; Ade Lia Ramadani; Qonita Rachmah (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackground: Diabetes mellitus is a chronic disease which if not done properly, can cause microvascular and macrovascular disorders. Indicators of the accuracy of diabetes management in this scientific article include education, self-management (improving diet, increasing physical activity, and self-efficacy), and monitoring of HbA1c levels. Mobile devices have the potential as a tool for diabetes mellitus management in the era of the industrial revolution 4.0.Purpose: to provide the latest information regarding the effectiveness of using mobile devices in controlling risk factors for diabetes mellitus.Method: This study is a literature review study. The electronic databases used are Google Scholar, Science Direct, and Directory of Access Journals (DOAJ). Inclusion criteria: original research, a journal of at least 80% indexed by Sinta (Indonesian journal) and indexed by Scopus (international journal), published year 2010-2020, intervention using a mobile device, has an output of HbA1c levels, self management (diet, physical activity, and self efficacy), and the level of knowledge. Exclusion criteria: reference with secondary data.Result: This study used 16 scientific articles. A number of 12 studies (75%) reported the use of mobile device applications in controlling risk factors for diabetes mellitus had significant measurement results in controlling HbA1c levels in 10 studies (83%) and 2 studies were not significant (17%). Outcomes in the form of self-management were reported by 9 studies with details of the significant results of dietary improvement in 5 studies (83%), increased physical activity in 5 studies (63%), and self-efficacy in 4 studies (67%). The increase in knowledge was reported by 4 studies with significant results (100%).Conclusion: Mobile device-based digital intervention is quite effective in controlling diabetes mellitus risk factors to control HbA1c levels, increasing self-management (improving diet, increasing physical activity, and self-efficacy) and knowledge.